2022
DOI: 10.3390/s22062096
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Graphical Algorithm of Sensor Distribution and Air Volume Reconstruction for a Smart Mine Ventilation Network

Abstract: The accurate and reliable monitoring of ventilation parameters is key to intelligent ventilation systems. In order to realize the visualization of airflow, it is essential to solve the airflow reconstruction problem using few sensors. In this study, a new concept called independent cut set that depends on the structure of the underlying graph is presented to determine the minimum number and location of sensors. We evaluated its effectiveness in a coal mine owned by Jinmei Corporation Limited (Jinmei Co., Ltd).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Through the joint implementation of sensors, artificial intelligence (AI), data analytics, Internet of Things (IoT), automation, augmented/virtual reality, robotization, and digital twins, it will be possible to simulate scenarios of mining production processes in real time, which will allow to analyze and study how different parameters or operating variables can modify or alter the performance of the mining operation, allowing this to go continuously from the real world to the meta-verse and return to the real world (physical–virtual–physical), making proactive decisions in favor of improving performance indicators [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the joint implementation of sensors, artificial intelligence (AI), data analytics, Internet of Things (IoT), automation, augmented/virtual reality, robotization, and digital twins, it will be possible to simulate scenarios of mining production processes in real time, which will allow to analyze and study how different parameters or operating variables can modify or alter the performance of the mining operation, allowing this to go continuously from the real world to the meta-verse and return to the real world (physical–virtual–physical), making proactive decisions in favor of improving performance indicators [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al ( 2022b ) studied optimal sensor placement for monitoring air distribution in mines, suggesting that equipping < 30% of tunnels with air velocity sensors ensures accurate air flow reconstruction if there are over 200 mine airways. Gao et al ( 2018 ) employed a modified genetic algorithm (GA) to solve the inverse air distribution problem, determining mine airway resistance from air flow and pressure measurements.…”
Section: Application Areas Of Ai Technologiesmentioning
confidence: 99%
“…In general, literature contains many works on the graphical methods for analyzing topologically complex mine ventilation networks (Maleki et al, 2018 ; Wu et al, 2019 ; Liu et al, 2022b ; Bosikov et al, 2023 ), but we do not discuss these works here, since they are not use AI technologies.…”
Section: Application Areas Of Ai Technologiesmentioning
confidence: 99%
“…To solve the airflow reconstruction problem, Liu et al [44] proposed a new algorithm of an independent cut set depending on the underlying graph structure and evaluated its effectiveness in practical applications. The results indicated that fewer than 30% of tunnels needed to have wind speed sensors set up to reconstruct the well-posed airflow of all the tunnels (>200 in some mines).…”
Section: Trends In Intelligent Minesmentioning
confidence: 99%